Public crises and personal threat - Breakwell, Glynis M.; Wright, Daniel B. (Sage Publishing, 2024)
With an emphasis on the practical, this book explains how people react to different sorts of crises, whether they be economic, environmental, health or war, and how we can better support the public, our families, and ourselves in future crises. The book interrogates how public crises are individualised, thought about, emotionally felt, and also mistrusted, all with a view to helping us understand some of the most difficult times we endure. Ideal for applied psychology students, public planning authorities and those specialising in crisis management this book will help us all to better understand the time we live in.